2016
DOI: 10.1002/term.2211
|View full text |Cite
|
Sign up to set email alerts
|

Towards reconstruction of epithelialized cartilages from autologous adipose tissue-derived stem cells

Abstract: Deformities of the upper airways, including those of the nose and throat, are typically corrected by reconstructive surgery. The use of autologous somatic stem cells for repair of defects could improve quality and outcomes of such operations. The present study explored the ability of paediatric adipose-derived stem cells (pADSCs), a readily available source of autologous stem cells, to generate a cartilage construct with a functional epithelium. Paediatric ADSCs seeded on the biodegradable nanocomposite polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…One highly tested synthetic polymer for adipose regeneration is Poly(e-caprolactone) (PCL), a biocompatible and biodegradable FDA approved polymer for medical devices [3]. Our group have modified PCL with polyhedral oligomeric silsesquioxane (POSS) nanoparticles to improve its hydrophobicity and inertness to form a nanocomposite polymer called POSS-PCL [4][5][6][7]. We have shown that POSS-PCL can support cell adhesion, proliferation and differentiation acting as an effective scaffold to support cell survival [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One highly tested synthetic polymer for adipose regeneration is Poly(e-caprolactone) (PCL), a biocompatible and biodegradable FDA approved polymer for medical devices [3]. Our group have modified PCL with polyhedral oligomeric silsesquioxane (POSS) nanoparticles to improve its hydrophobicity and inertness to form a nanocomposite polymer called POSS-PCL [4][5][6][7]. We have shown that POSS-PCL can support cell adhesion, proliferation and differentiation acting as an effective scaffold to support cell survival [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Our group have modified PCL with polyhedral oligomeric silsesquioxane (POSS) nanoparticles to improve its hydrophobicity and inertness to form a nanocomposite polymer called POSS-PCL [4][5][6][7]. We have shown that POSS-PCL can support cell adhesion, proliferation and differentiation acting as an effective scaffold to support cell survival [4][5][6][7]. However, a successful biodegradable scaffold for adipose tissue engineering must integrate with the surrounding host tissue by integrating by laying down extracellular matrix and angiogenesis without causing an immune response or capsule formation to degrade effectively with time.…”
Section: Introductionmentioning
confidence: 99%
“…Act 1986 using fertilized brown Leghorn eggs (Needle Farm, UK) as previously described. 25 Pediatric hADSCs encapsulated in 2 mm fibrin scaffolds were cultured in control or osteogenic differentiation media for 2, 3, or 4 weeks prior to CAM grafting for 7 days and analyzed in parallel with scaffolds maintained in culture for the total length of the experiment (3,4, and 5 weeks). Cells from three different patient lines were used (n ≥ 3 per line for each condition).…”
Section: Cam-grafting Was Carried Out Under the Animals Scientific Prmentioning
confidence: 99%
“…The successful isolation of stromal vascular fraction (SVF) from adipose tissue with these devices has already been seen in a number of clinical trials and treatments for tissue repair. Although much advancement in ADSC research has been made in the last few years, more innovation in successful ADSC translation is needed [4][5][6][7].…”
Section: Editorialmentioning
confidence: 99%